A novel current measurement offset error compensation method based on the adaptive extended state observer for IPMSM drives - Zuo, Yun (2023)
Offset error from the measured phase current mostly causes a performance afflicted for interior permanent-magnet synchronous motor (IPMSM) drives, and innovative solutions are eagerly sought. Considering this, this article proposes an adaptive extended state observer (AESO) to compensate the current measurement offset error (CMOE) without additional hardware. In the proposed scheme, the AESO is designed in a stationary coordinate system to estimate CMOE in dc form. Notably, the proposed AESO possesses a second-order low-pass filtering characteristics. With this, the proposed method shows a high robustness against the disturbances from the ac components caused by motor parameter changes, etc. Furthermore, the adaptive gains enable the proposed scheme to maintain a satisfactory performance under the motor frequency changes. The feasibility of the proposed scheme is thoroughly verified by extensive experimental tests based on the test bench of a 3-kW IPMSM drives.